Sedimentary evolution of a Permo-Carboniferous succession in southern Bolivia: Responses to icehouse-greenhouse transition from a probabilistic assessment of paleolatitudes - Gallo, Leandro César; Dalenz Farjat, Alejandra; Tomezzoli, Renata Nela; Calvagno, Juan Martín; Hernández, Roberto Mario (Journal of South American Earth Sciences)
The Permo-Carboniferous encompasses the deterioration of the Late Paleozoic Ice Age (LPIA), one of the most important glacial events in Earth's history. However, the key drivers behind the demise of the ice sheets remain controversial. Recent advances attained from high precision zircon ages provide chronostratigraphic frameworks for key basins across Gondwana, but the location and geographic extent of ice centers in west-central Gondwana remain ambiguous. Permo-Carboniferous strata from the Tarija Basin in southern Bolivia are analogous to many late Paleozoic basins across South America and provide key evidence regarding the LPIA and its demise. Detailed sedimentologic data from the Mandiyutí and Cuevo Groups exposed in the Iñiguazú anticline shows a pattern of climate-sensitive facies that records a shift from cold-humid to warm-arid conditions, in accordance with the long-term transition from icehouse-to-greenhouse conditions widely recognized across western Gondwana. Although it has been long recognized that the main drivers behind the LPIA establishment resulted from past latitudinal plate motions over the polar regions, the northward drift of Gondwana away from the South Pole remains poorly constrained owing to debates around the paleogeography of Pangea. Here, from a thorough probabilistic assessment of paleomagnetic data, we have determined a robust estimator of the varying paleolatitude through the late Paleozoic that provides a much needed paleolatitudinal framework for the Tarija basin. Independent evidence from the paleomagnetic analysis has shown that the Tarija basin was within the polar circle for the Upper Devonian but started to move rapidly towards the equator during the Carboniferous and remained essentially isolatitudinal throughout the Permian. According to these findings, we conclude that the key driver controlling the icehouse-greenhouse transition in this region was the continental drift of Gondwana across zonal climate belts. Fil: Gallo, Leandro César. Consejo Nacional de ...